Arsitektur Komunikasi untuk Mitigasi Risiko dalam Prostitusi Digital: Studi Etnografi pada Aplikasi MiChat - Victoria Simon Suripatty; Bambang Sukma Wijaya (IAI Nasional Laa Roiba Bogor, 2026)
The development of digital technology has transformed prostitution practices from physical spaces to digital platforms, where actors must operate amidst the absence of formal protection and legal threats. This study aims to describe the communication patterns and strategies used by commercial sex workers (CSWs) in offering services through MiChat, employing the ethnographic communication approach with the SPEAKING model (Saville-Troike, 2003). This research employs a qualitative approach. Data were obtained through digital observation, in-depth interviews with CSWs, service users, and pimps in the Greater Jakarta area, as well as documentation of transactional conversations on MiChat. Data were analyzed through three stages: data condensation, data display, and conclusion drawing. The findings reveal that CSW communication on MiChat constitutes a Communication Architecture for Risk Mitigation—a structured system that compensates for the formal protection absent from the platform. This system operates through a four-stage Repeated Communication Model: self-representation, initiation and selection, negotiation and confirmation, and meeting and termination. Each conversation stands as an independent and anti-relational event as a safety strategy. The study also identifies three roles (CSWs as passive waiters, clients as active initiators, and pimps as optional filters behind the scenes), the use of coded language such as ST (Short Time) and LT (Long Time) along with emojis, tonal shifts from neutral to firm to cold as negotiation boundaries, and unwritten norms such as direct communication, rapid response, and privacy as a necessity. All these elements function to mitigate three spectrums of risk: legal risks (avoiding detection and raids), physical risks (violence and exploitation), and economic risks (fraud and unilateral cancellation).